دور مكتبة مصر العامة فى نشر الوعي السياحي بمحافظة الاقصر: دراسة حالة - منال غريب يسن المصرى المصرى (المجلة الدولية لعلوم المكتبات والمعلومات)
The study aims to identify the role of the Egyptian public library in spreading tourism awareness and educating the Luxor community and monitor the tourist attractions of Egypt’s public library. The study was based on the case study method to monitor the extent of the study community’s awareness of the role of the Egyptian public library in supporting the tourism sector through the activities and services provided by the library this was done by using the questionnaire tool that was directed to the frequent Visitors to the library according to their age groups educational level and place of residence. The researcher also used the interview tool for some employees and officials of the Egyptian public library in Luxor. The study found that 96% from the study sample, the public library of Egypt has prominent role in spreading cultural and tourism awareness while 4% just don’t see it. The role of the library in spreading this awareness is to” Enjoy watching the heritage festivals of Luxor Governorate ”. The most common source of awareness among the sample with percentage of 70% in the second place”The library provides me with the use of Egyptology hall in the library whether by viewing or photographing with a rate of 89%. Among the study’s recommendations is the need for coordination between the ministries of education and tourism in order to prepare simplified methods for young people and students of schools and universities to raise awareness of the importance of the tourism industry